Ruthenium(II) complexes bearing benzimidazole-based N-heterocyclic carbene (NHC) ligands as potential antimicrobial, antioxidant, enzyme inhibition, and antiproliferative agents. Issue 5 (30th June 2022) - Boubakri, Lamia; Chakchouk-Mtiba, Ahlem; Naouali, Olfa; Mellouli, Lotfi; Mansour, Lamjed; Özdemir, Ismail; Yaser, Sedat; Sauthier, Mathieu; Hamdi, Naceur
Abstract: In this work, new substituted benzimidazolium salts 2a–d having different groups on the side chain have been synthesized and reacted with Ag2 O to produce Ag(I) N-heterocyclic carbene (NHC) complexes 3a–d . Ag(I)-NHC complexes were used as a carben transfer agents to synthesize ruthenium(II)-NHC complexes 4a–d . The structures of all compounds were characterized by 1 H NMR, 13 C NMR and FT-IR spectroscopies and elemental analysis. The IC50 values of these complexes were determined by MTT assay against MCF7, MDA-MB-231 and HF cancer cell lines. The lowest MIC values were obtained for two complexes, 4b and 4d . The Ru(II)-NHC complexes generally triggered stronger bacterial growth inhibition than the metal-free benzimidazolium cations. Enzymatic inhibition investigation against acetylcholinesterase (AChE) and tyrosinase (TyrE) showed that 4b and 4d are the most potent inhibitors against AchE with an IC50 of 2.52 and 5.06 µg mL −1, respectively, and against TyrE with an IC50 of 19.88 and 24.95 µg mL −1, respectively. Antioxidant activity of the synthesized NHC ligands 2a–2d and their respective Ru(II)-NHC complexes 4a–4d was assessed by three different techniques: the 2.2-diphenyl-1-picrylhydrazyl (DPPH), the 2.2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radicals scavenging and the β-carotene linoleic acid bleaching assay, showing that 4d has recorded an important antioxidant activity. Graphical Abstract: UF0001